Ultra‐thin barrier quaternary InAlGaN HEMTs with state of the art sheet resistance. Issue 3 (20th March 2014) - Gao, Xiang; Pan, Ming; Gorka, Daniel; Oliver, Mark; Schuette, Michael; Ketterson, Andrew; Saunier, Paul
Abstract: We report transport properties measured from quaternary barrier InAlGaN high electron mobility transistor wafers on SiC substrates. With similar barrier thicknesses, higher mobility and sheet charge density were both demonstrated by a strained barrier quaternary In0.07 Al0.75 Ga0.18 N HEMT comparing to a ternary In0.17 Al0.83 N HEMT with lattice matched barrier to the GaN buffer. With 1 nm AlN interlayer, sheet resistances of 218 Ω/□ and 228 Ω/□ were obtained from 4.8 nm and 4.4 nm barrier structures, respectively. Both structures also show excellent electron motilities. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)